STUDENTS’ ENGLISH SPEAKING SKILL AND ACTIVATION METHOD: THE CASE OF ONE SENIOR HIGH SCHOOL - Tria Novita (Edukasi, 2017)
This study was aimed to find out whether or not: (1) there was a significant improvement on the eleventh grade students’ speaking skill who were taught by using activation method at MAN 3 Palembang before and after the treatment; and (2) there was a significant difference on the eleventh grade students’ speaking skill who were taught by using activation method and those who were not at MAN 3 Palembang. In this study, 60 eleventh grade students at MAN 3 Palembang were chosen as the sample. The students were grouped into two (i.e.: experimental group and control group). Experimental group consisted of 30 students, and control group consisted of 30 students. The experimental group was taught by using activation method, and the control group was taught by using teacher’s method. The data were collected by giving pretest and posttest to both groups. To analyze the data, paired sample t-test and independent sample t-test were used. The result of paired sample t-test showed that there was a significant improvement in students’ speaking skill for the experimental group. Independent sample t-test analysis showed that there was a significant difference in both of groups who were taught by using the activation method and those who were not (teacher’s method).